Personality traits as predictors of anxiety and aggression in contrasted groups: clinical and non-clinical (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The present work aimed to investigate the influence of personality traits, especially neuroticism, in levels of anxiety and aggressiveness displayed in contrasted groups (clinical and non-clinical). This research relied on a sample of 113 individuals, 49 (43.4%) males and 64 (56.6%) females, aged between 18 to 57 (M = 25,32; DP = 8,80). Three psychometric scales of measurement were used: IGFP-5, STAXI-2, and BAI. The data collection occurred in two federal public universities from two state capitals, Maceió and Belo Horizonte (non-clinical group), and also in school clinics and private clinics in Maceió (clinical group). Single differences were integrated – the big five personality factors (BFF) – in relation to statistical and psychobiological factors, assuming that personality traits overlap themselves and are responsible for the maturation and constant flexibility in the development of personality for having genetic factors in connection with environmental aspects. The conclusions suggest that neuroticism (IGFP-5) is positively correlated with anxiety (BAI), some aspects of the aggressiveness (STAXI-2), and aggressive response control (outwards and inwards aggressiveness of Staxi-2), which can be related to inability in the inhibitory control
Keywords: Personality Traits; Neuroticism; Anxiety; Aggressiveness